Voice Control Turn-Based Role Playing Game Development Using Unity Speech Recognition - Sebastian, Sebastian; Dirgantara, Harya Bima (Universitas Multimedia Nusantara, 2023)
This research endeavors to create and develop a turn-based role-playing video game utilizing speech recognition as an innovative means to introduce a novel experience in video games. The game is designed and implemented using the Unity game engine. The game prototype produced in this study is intended to provide a unique experience when playing games, namely using voice recognition to try to beat opponents. The researcher adopts the Extreme Programming methodology, compassing four stages: Planning, Design, Develop and Testing/Release. The culmination of this research is a turn-based role-playing game featuring speech recognition controls intended for Windows computers equipped with a microphone. The game offers players fresh and innovative gameplay by incorporating speech recognition. Based on the closed beta trial on three respondents, the result was that there was an influence from the playing room. Two words are difficult for the game to detect: